Analyzing Adaptation of MNC Portal Indonesia Internship Students in Facing Culture Shock - Hartini, Tin; Piernawan, Fajar Ramdani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
College students who undergo internship activities often experience culture shock due to entering a new environment that has cultural differences with their home culture. Culture shock can cause a variety of reactions, including discomfort with the new environment. Intercultural communication, as an interaction between individuals who come from different cultural backgrounds can be an important element in overcoming this problem. The research method is a qualitative research method with a descriptive approach. Data collection research methods with five informants and one key informant through interviews and documentation. The data analysis techniques used are data reduction, data presentation and conclusions. The data validity used is source triangulation. The results of this study indicate the occurrence of culture shock experienced by several internship students at MNC Portal Indonesia in four stages of cultural adaptation, namely honeymoon, frustration, readjustment and resolution. Differences in lifestyles, ways of communication, as well as responsibilities and targets achieved in the work that resulted in internship students experiencing culture shock while doing internships at MNC Portal Indonesia. However, interns choose to survive and face all the conditions that exist, so that all interns are able to adapt to the new environment, and get benefits after doing an internship at MNC Portal Indonesia.